Evidence of lowlife satisfaction among undergraduates in Southwest Nigeria (2012)
The paper examined satisfaction with life among 1429 undergraduates from Southwestern Nigeria. Ex post focto survey design was adopted and convenient sampling method was used. Four hundred and seventy five (475, i.e. 33.2%) males and 953 (66.8%) females, ages ranging between 16 to 27 years (M=28.47, SD = 8.76). Validated scale was used for data collection and the two hypotheses stated were confirmed after testing with appropriate statistics. A total of 837 undergraduates (58.57%) had scores less than the midpoint of 20; their mean was 14.03 (SD = 2.42). 88 (6.2%) scored exactly 20, while 504 (35.33%) scores were higher than 20. Conclusion was reached that undergraduates have low satisfaction with life and there is no significant difference between males and females regarding satisfaction with life. There is need for further research to find out the factors that account for low satisfaction with life among this sample